Adaptive strategies of sponges to deoxygenated oceans. (18th December 2021) - Micaroni, Valerio; Strano, Francesca; McAllen, Rob; Woods, Lisa; Turner, John; Harman, Luke; Bell, James J.
Abstract: Ocean deoxygenation is one of the major consequences of climate change. In coastal waters, this process can be exacerbated by eutrophication, which is contributing to an alarming increase in the so‐called 'dead zones' globally. Despite its severity, the effect of reduced dissolved oxygen has only been studied for a very limited number of organisms, compared to other climate change impacts such as ocean acidification and warming. Here, we experimentally assessed the response of sponges to moderate and severe simulated hypoxic events. We ran three laboratory experiments on four species from two different temperate oceans (NE Atlantic and SW Pacific). Sponges were exposed to a total of five hypoxic treatments, with increasing severity (3.3, 1.6, 0.5, 0.4 and 0.13 mg O2  L −1, over 7–12‐days). We found that sponges are generally very tolerant of hypoxia. All the sponges survived in the experimental conditions, except Polymastia crocea, which showed significant mortality at the lowest oxygen concentration (0.13 mg O2  L −1, lethal median time: 286 h). In all species except Suberites carnosus, hypoxic conditions do not significantly affect respiration rate down to 0.4 mg O2  L −1, showing that sponges can uptake oxygen at very low concentrations in the surrounding environment. Importantly, sponges displayed species‐specific phenotypic modifications in response to the hypoxic treatments, including physiological, morphological and behavioural changes. This phenotypic plasticity likely represents an adaptive strategy to live in reduced or low oxygen water. Our results also show that a single sponge species (i.e., Suberites australiensis ) can display different strategies at different oxygen concentrations. Compared to other sessile organisms, sponges generally showed higher tolerance to hypoxia, suggesting that sponges could be favoured and survive in future deoxygenated oceans. Abstract : Ocean deoxygenation is one of the major consequences of climate change and eutrophication. Here, we experimentally assessed the response of four temperate sponges to simulated hypoxic events. We found that sponges are generally very tolerant of hypoxia. For all the species investigated, lethal thresholds are lower than 0.5 mg O2  L −1 . Sponges displayed species‐specific phenotypic modifications in response to the hypoxic treatments, which likely represent adaptive strategies to live in reduced oxygen conditions. Compared to other sessile organisms, sponges generally showed higher tolerance to hypoxia, suggesting that sponges could be favored in future deoxygenated oceans.